Eksplorasi Bakteri Penghasil Eksopolisakarida dari Rizosfer Kelapa Sawit sebagai Pemantap Agregat Tanah [Exploration of exopolysaccharide-producing bacteria from Oil Palm Rhizosphere as a Soil Aggregate stabilizer] - Nuni Gofar; Diana Utama (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Palm oil cultivated in sandy or sandy loam with aggregate not stable and easily eroded, will lack water and nutrients. To increase sandy soil aggregation, soil aggregate stabilizing agents must be added, one of which is exopolysaccharideproducing bacteria.This study aimed to explore exopolysaccharide-producing bacteria from the oil palm rhizosphere and analyze their ability to form soil aggregates. Bacterial exploration was carried out by isolating bacteria from various age groups of oil palm rhizosphere, then isolates were selected which were able to produce the best exopolysaccharide, then tested it ability in stabilizing the soil aggregate. Bacterial selection and isolation was carried out in the Soil Biology Laboratory, Department of Land, Faculty of Agriculture, Sriwijaya University. The results showed that six isolates had the potential to produce exopolysaccharide (S1A, S3A, S3B, S4A, S4B and S4C) characterized by the presence of thick slime and produce exopolysaccharide. Based on the calculation of exopolysaccharide weight, S4C isolates from oil palm rhizosphere samples over the age of 10 years were able to produce the best exopolysaccharide weight of 44.25 g mL-1. After 2 months incubation, the soil which was inoculated with S4C bacteria had very stable aggregates (excellent physical quality) which differed significantly compared to soil aggregates without bacterial inoculation (poor physical quality).It is recommended to continue the study of the ability of S4C isolates to increase aggregation and water and nutrient retention in soils with high sand content. ABSTRAKTanaman kelapa sawit yang dibudidayakan pada tanah berpasir atau lempung berpasir dengan kemantapan agregat rendah dan mudah tererosi, akan kekurangan air dan unsur hara. Untuk meningkatkan agregasi tanah berpasir, harus ditambahkan agen pemantap agregat tanah, salah satunya adalah bakteri penghasil eksopolisakarida. Penelitian ini bertujuan untuk mengeksplorasi bakteri penghasil eksopolisakarida asal rizosfer kelapa sawit dan menguji kemampuannya dalam membentuk agregat tanah. Eksplorasi bakteri dilakukan dengan mengisolasi bakteri dari rizosfer kelapa sawit berbagai umur, kemudian dipilih isolat yang mampu menghasilkan eksopolisakarida terbaik, lalu menguji kemampuannya dalam memantapkan agregat tanah. Seleksi dan isolasi bakteri dilakukan di Laboratorim Biologi Tanah, Jurusan Tanah, Fakultas Pertanian, Universitas Sriwijaya. Hasil penelitian menunjukkan enam isolat berpotensi menghasilkan eksopolisakarida (S1A, S3A, S3B, S4A, S4B dan S4C) ditandai dengan adanya slime tebal dan menghasilkan eksopolisakarida. Berdasarkan perhitungan bobot eksopolisakarida, isolat S4C asal sampel rizosfer kelapa sawit berumur lebih dari 10 tahun mampu menghasilkan bobot eksopolisakarida terbaik yaitu 44,25 g mL-1. Setelah diinkubasi 2 bulan, tanah yang diinokulasi bakteri S4C memiliki agregat dengan kualitas fisik sangat baik yang berbeda sangat nyata dibandingkan agregat tanah tanpa diinokulasi bakteri (kualitas fisik buruk). Disarankan untuk melanjutkan kajian kemampuan isolat S4C dalam meningkatkan agregasi serta retensi air dan hara pada tanah dengan kadar pasir yang tinggi.